2019
DOI: 10.1097/md.0000000000015560
|View full text |Cite
|
Sign up to set email alerts
|

The association and diagnostic value of red blood cell distribution width in colorectal cancer

Abstract: Red blood cell distribution width (RDW) is associated with several diseases. However, the diagnostic value of RDW and its related factors remain unclear in colorectal cancer (CRC). This single-center retrospective study evaluated 211 Chinese CRC patients and 103 healthy controls. The association of RDW with the clinical parameters of CRC, as well as its correlations with carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) were analyzed. The diagnostic value of RDW alone or combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Similarly, high RDW was found to be associated with worse overall survival by Kust et al (7) in a retrospective study of 90 patients with CRC; however, this relationship was only present in subjects with stage II cancer. Several other studies have also shown similar results (1,4,31). In this study, we also showed that the preoperative mean RDW values of patients who died during postoperative followup were significantly higher than those who survived.…”
Section: Resultssupporting
confidence: 89%
“…Similarly, high RDW was found to be associated with worse overall survival by Kust et al (7) in a retrospective study of 90 patients with CRC; however, this relationship was only present in subjects with stage II cancer. Several other studies have also shown similar results (1,4,31). In this study, we also showed that the preoperative mean RDW values of patients who died during postoperative followup were significantly higher than those who survived.…”
Section: Resultssupporting
confidence: 89%
“…Our study supported the view that indicators including HGB, MCV, and MCHC were worse in colon cancers. Previous reports, including ours, had highlighted the adverse prognostic warning of CRC at excessive RDW-CV level [17,54] . Based on the previous conclusions, the results of this study again utilized and expanded the significance of high RDW-CV in peripheral blood of CRC.…”
Section: Discussionmentioning
confidence: 50%
“…Similarly to mSEPT9, the sensitivity of TuM2-PK was higher for more advanced cancers (Dukes’ stage C and D; stages III and IV) and lower when it was used to detect adenomas, polyps or dysplasia. All three studies included in the meta-analysis compared the diagnostic performance of TuM2-PK to the established stool marker FIT, and demonstrated that FIT was preferable to TuM2-PK as a faecal biomarker for screening populations [ 94 , 116 , 117 ]. Three studies [ 50 , 67 , 115 ] evaluated TuM2-PK as a blood-based biomarker in combination with other markers or in panels, and all found sensitivity to be higher for TuM2-PK in combination with other markers.…”
Section: Discussionmentioning
confidence: 99%